Perencanaan dan Perancangan Baitul Maal An-Nur di Kelurahan Setia Mekar - Sumardi, Fitriani; Fitri Astuti, Retno; Sakhrial Pradini, Purnama; Aji Prasetyo, Sutrisno; Herol (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Kelurahan Setia Mekar in Kabupaten Bekasi is experiencing rapid development in economic and infrastructure aspects, which results in an increase in the need for space for social and religious activities. Jami' An-Nur Mosque, as a center for religious activities, facing limited space to accommodate zakat activities, infaq and alms. To solve this problem, it is planned to build Baitul Maal near the mosque. This project involved the Community Service team from the Architecture Study Program of Pelita Bangsa University who designed the architectural plans for Baitul Maal An-Nur. The method used includes Focus Group Discussion (FGD), Function Identification, Site Analysis, environmentally friendly, inclusive and sustainable architectural design planning. The results achieved include building designs that are efficient, accessible and meet the needs of the local community. This program provides a sustainable solution for managing zakat and religious activities and becomes a model for community and academic collaboration in developing social infrastructure.